Differential gene expression analysis of papillary thyroid carcinoma reveals important genes for lymph node metastasis - Wan Fahmi Wan Mohamad Nazarie; Azliana Mohamad Yusof; Francis Yew Fu Tieng; Nur Fadhlina Mohamad Pakarulrazy; Rohaizak Muhammad; Shahrun Niza Abdullah Suhaimi; Nani Harlina Md Latar; Sazuita Saidin; Isa Mohamed Rose; Learn-Han Lee; Nurul-Syakima Ab Mutalib (Progress in Microbes and Molecular Biology)
Background: Papillary thyroid carcinoma (PTC) is the most prevalent thyroid cancer. We explored the differential gene expression (DEG) of the transcriptional regulation in thyroid cancer with the main aim of determining the genes involved in lymph node metastasis (LNM) in PTC. Methods: We employed a bioinformatics pipeline for RNA-Seq analysis in PTC with and without LNM at the gene expression level. We performed read mapping, read quantitation, and DEG analysis using STAR, Cufflinks, and Cuffdiff, respectively. Subsequently, functional annotation and pathway enrichment were carried out using FunRich (functional enrichment analysis tool). Results: Expression profiling revealed changes in the PTC with LNM (33 genes at p-value < 0.05 and log2 fold change |1.0|) compared to the adjacent normal thyroid, whereas 69 genes showed differential expressions in the PTC with lymph node negative (LNN) versus adjacent normal thyroid. We identified 31 significant DEGs in PTC LNM versus PTC LNN; and 44 significant DEGs between adjacent normal thyroid tissues from PTC LNM and PTC LNN. The biological processes of genes expressed at higher levels in PTC LNM compared to PTC LNN were involved in cell communication, energy pathway, and metabolism, whereas ion transport, energy pathways, and regulation of nucleobase, nucleoside, nucleotide, and nucleic acid metabolisms, were downregulated. Conclusion: These findings provide further evidence for the role of cellular transport regulatory processes in metastatic disease.